Promising winter durum wheat varieties and their seed production - T. S. Bezuglaya; N. E. Samofalova; N. P. Ilichkina; A. S. Ivanisova; N. V. Kabanova; M. M. Kopus (Зерновое хозяйство России, 2022)
The main task of agricultural producers has always been and still remains to obtain high and stable yields, which can be provided by new developed varieties, which are the main reserve for increasing grain production. The current paper has presented the study results of the work in 2018–2021, namely, the development of promising varieties and the main features of seed production. The purpose of the study was to estimate promising winter durum wheat varieties according to the main economic and biological traits and properties, quality indicators of grain and pasta, and seed production features. The studied varieties were able to give consistently high yields (from 5.56 to 12.67 t/ha), combining the main economic and biological traits (drought resistance, frost resistance, resistance to major diseases and lodging) and quality indicators of grain and pasta. The study of the physicochemical properties of grain showed that the winter durum wheat varieties met the requirements of GOST 9353-2016 and belonged to the 1–2 quality classes, which was quite enough to produce good pasta and cereal. The pasta color of the varieties ‘Yakhont’, ‘Yantarina’, ‘Uslada’ was yellow (4.3–4.6 points); it was creamy in the variety ‘Yubilyarka’ (3.5 points); the content of carotenoids varied from 507 µg/% (the variety ‘Yubilyarka’) to 610 µg/% (the variety ‘Uslada’). In order to preserve and maintain the main features and properties characteristic for each variety, their seed production is being currently carried out with a comprehensive estimation of both phenotypic (approbation) traits and genotypic ones using protein markers. The varieties ‘Yakhont’, ‘Yubilyarka’, ‘Yantarina’ and ‘Uslada’ have clearly distinguishable spectra of gliadins 3.2.3T2, 13.2T+6T.3.T1, 5.2.4T1 and 13X.4T.3.2, which makes it possible to control their varietal purity at all stages of seed production.